Rationalization of Internal Transport Operation in the Intermodal Transport Terminal - Marian Sulgan; Jarmila Sosedova (Communications - Scientific letters of the University of Zilina, 2016)
This paper presents the results of investigation of the possibilities for creating the internal circuit for the handling and moving the containers on the territory of intermodal transport terminal. It utilizes the theoretical knowledge from the investigation of queuing systems and the theory of stochastic processes.